The equity gap and knowledge-based firms - Wilson, Nick; Wright, Mike; Kacer, Marek (Journal of Corporate Finance, 2018)
The equity gap, the difference between the amount of (risk) capital that would be invested under conditions of well-informed and competitive markets and the amount of capital actually invested, covers both startups and ventures moving beyond startup to the establishment and early growth phase. We provide estimates for the size of the equity gap for firms facing later stage financing issues, the second equity gap. This ‘second’ equity gap relates to a second so-called ‘valley of death’ in financing the growth phase, and is particularly pertinent for knowledge-intensive (KI) firms. We utilize a unique panel database covering the population of limited companies, which includes 2852 VC backed companies and 4048 deals. Using propensity scoring methods and multivariate models determining investment demand we screen the corporate population for potential VC investments and estimate the size of the equity gap in total and the KI firms that face, potentially, the second equity gap as a subset of our total estimates.